PENGARUH KOMPETENSI GURU TERHADAP KINERJA DI SMP AL-FURQAN TEBUIRENG JOMBANG TAHUN AJARAN 2023/2024 - Dhiyarifki Muhtaromi; Khoirul Umam (Kampus Akademik Publiser, 2024)
Education is basically an effort to provide certain knowledge, insights, skills and expertise to individuals. A person's skills must be given knowledge by an educator or teacher, which is an important component of the educational process. One thing that a teacher must have in achieving learning and educational goals is competence. A teacher's performance can be influenced by how much the teacher masters the competencies that must be met to become an educator. As a teacher, the teacher must have many ways and methods to stimulate students to be active in learning. This research aims to determine: (1) Teacher competency at Al-Furqan Tebuireng Middle School, Jombang; (2) Teacher performance at Al-Furqan Tebuireng Middle School, Jombang; (3) The influence of teacher competency on performance at Al-Furqan Tebuireng Middle School, Jombang. This research uses a quantitative approach with an ex-post facto type of research. This research is a population study because there are less than 100 subjects, totaling 57 teachers. Data collection techniques use observation, questionnaires and documentation. Test the validity of the instrument using Person Product Moment correlation and test reliability using the Cronbach's Alpha formula. Meanwhile, prerequisite analysis tests include normality tests and correlation tests. Hypothesis testing includes a simple linear regression equation. Based on the research results, it shows that: (1) Teacher Competency, it is known that a small number with low criteria received a minimum score of 104-117, totaling 4 respondents with a score of 7%, the majority of teacher competency with fairly good criteria received a score of 118-131, totaling 38 respondents with a score of 66.7%, and some teacher competencies with good criteria received a score of 132-145, totaling 15 respondents with a score of 26.3%; (2) Teacher performance shows that a small number with low criteria got a minimum score of 80-91, totaling 14 respondents with a score of 26.6%, the majority of teacher performance with fairly good criteria got a score of 92-103, totaling 33 respondents with a score of 57.9%, and some teachers' performance with good criteria received a score of 104-116, totaling 10 respondents with a score of 17.5%; (3) The results of a simple linear regression test show that there is an influence between Teacher Competency on Teacher Performance at Al-Furqan Tebuiremg Jombang Middle School. The magnitude of the influence is 60.4% while the remaining 39.6% is influenced by other variables not included in this model.